(untitled) (Research, Society and Development, 2020)
The goals of the present study were i) to estimate the prevalence of excess weight and obesity in pregnant women who were admitted at a highly complex public hospital in 2017, and ii) to examine the profile of these participants. This is a cross-sectional, descriptive study. Complete medical records were available from 289 out of 421 participants and were included in analysis. The prevalence of excessive weight during pregnancy was 26% (95% CI: 20.8 – 30.9) and 41% met the criteria for obesity (95%CI: 35.1 – 46.5). Regression analyses indicated that body mass index (BMI) before pregnancy (β = 20.106, p < .001) and newborn’s weight (β = 2.277, p = .024) were significant in predicting excess weight in pregnancy, in a model explaining 70.2% of gestational BMI. The work contributes to the understanding of excess weight and obesity in pregnant women and might be useful in planning actions with the purpose of reducing complications in gestational and perinatal phases. Moreover, data could support strategies aiming to improve the outcomes of pregnancies, especially in the studied service.